Suitability of Mangrove Forests for Sustainable Tourism - Kevin Ewaldo; Mahawan Kurniasa; Noverita Dian Takarina (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2023)
The Pantai Indah Kapuk (PIK) Mangrove Ecotourism is in DKI Jakarta Province. It can develop into sustainable tourism because it has good natural conditions and an easy-to-reach location. This research aims to determine the suitability index of mangrove forest tourism for sustainable tourism development. This research was conducted from February to March 2023. The method used in this research is a quantitative descriptive method. This study has two observation points to determine the thickness, density, type of vegetation, and biota objects. The results showed that this location has the potential to be used as a tourist attraction. It is supported by the value of the tourism suitability index for each research station of 68.7% at the first observation station and 62.5% at the second observation station. Rhizphora apiculata species dominate the composition of the mangrove vegetation in this location, with a density of 850 trees/ha. The thickness of the mangrove at this location is 60.4 m at the first station and 64.1 m at the second station. The biota objects found at the observation point were fish, mollusks, reptiles, and mammals. Overall, this research location is suitable for tourist attractions and can be developed to become more sustainable tourism. However, several efforts are needed to improve this suitability, such as mangrove forest rehabilitation and cooperation from various stakeholders.